Erosion behavior of W-Ta coatings in plasmas of stationary mirror Penning discharges - Belous, V.A.; Bondarenko, M.N.; Glazunov, G.P.; Ilchenko, A.V.; Kuprin, A.S.; Konotopskiy, A.L.; Lunyov, V.M.; Ovcharenko, V.D. (Вопросы атомной науки и техники, 2017)
Investigations had been carried out of the influence of Ta alloying (2…16 wt.%) in W-coatings on their erosion behavior in steady state plasmas of Penning discharges in different gases: argon, nitrogen, and hydrogen. The coatings were deposited on stainless steel substrates by argon ion sputtering of targets made from appropriate metals. For comparison the erosion behavior had been examined of pure W and Ta coatings obtained by the same method. It was shown the essential decrease of an erosion rate after Ta addition in W coatings. The possible physical mechanism is suggested to explain such erosion behavior.